Democratic Republic of São Tome and Príncipe : Financial Sector Development Implementation Plan, 2017-2019 - World Bank (World Bank, Washington, DC, 2016)
The main objective of this report is to contribute to the development of São Tomé and Príncipe’s financial sector and provide its Government and private stakeholders with a clear roadmap for reform in key policy areas, particularly regarding efforts to strengthening financial sector soundness, enhance financial inclusion, and upgrade existing financial infrastructure. The report includes a sequenced implementation plan designed to enable the authorities to implement critical financial sector reforms and interventions, designed to foster a more efficient, sound and inclusive financial sector in São Tomé and Príncipe based on a coherent policy framework.